1981
DOI: 10.1007/bf02214969
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of thermophilic campylobacters from two populations of dogs

Abstract: Faecal samples were collected from newly impounded stray dogs and from dogs presented to a clinic by their owners. The dogs were categorised as strays or pets and their faeces as formed or unformed. The faeces were examined bacteriologically. Campylobacters were significantly (P less than 0.01) more frequently isolated from the faeces of the stray dogs but there was no significant difference between the frequency of isolation of the organism from formed or unformed faeces. The significance of this finding in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
1

Year Published

1983
1983
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
3
3
1
Order By: Relevance
“…In the present study, the frequency of stray dogs harboring Campylobacter species was of 51.3%. This value is similar to that obtained by Simpson et al 13 . and Bruce and Zochowski 3 for the same type of animals.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, the frequency of stray dogs harboring Campylobacter species was of 51.3%. This value is similar to that obtained by Simpson et al 13 . and Bruce and Zochowski 3 for the same type of animals.…”
Section: Discussionsupporting
confidence: 93%
“…and Bruce and Zochowski 3 for the same type of animals. On the other hand, as Simpson et al 13 . have found, this study showed that the number of animals with Campylobacter in their feces was significantly greater in stray than in pet dogs.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, it was simmilar to that reported by SIMPSON et al 29 in stray dogs (52.6%) in England. Remarkable differences exist in the incidence of intestinal carriage of Campylobacter among stray and pet dogs 2 .…”
Section: Discussionsupporting
confidence: 81%
“…Remarkable differences exist in the incidence of intestinal carriage of Campylobacter among stray and pet dogs 2 . 29 Although all the dogs studied had an individualized owner, many of them presented loiterer habits reflecting a poor standard of canine hygiene that predisposes to intestinal colonization with Campylobacter 30 .…”
Section: Discussionmentioning
confidence: 99%